2021
DOI: 10.1080/07391102.2021.1958061
|View full text |Cite
|
Sign up to set email alerts
|

Evolving ribonucleocapsid assembly/packaging signals in the genomes of the human and animal coronaviruses: targeting, transmission and evolution

Abstract: A world-wide COVID-19 pandemic intensified strongly the studies of molecular mechanisms related to the coronaviruses. The origin of coronaviruses and the risks of human-to-human, animal-to-human, and human-to-animal transmission of coronaviral infections can be understood only on a broader evolutionary level by detailed comparative studies. In this paper, we studied ribonucleocapsid assembly-packaging signals (RNAPS) in the genomes of all seven known pathogenic human coronaviruses, SARS-CoV, SARS-CoV-2, MERS-C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 104 publications
(133 reference statements)
1
2
0
Order By: Relevance
“…An elegant study employing all four structural proteins to produce viral‐like particles (VLPs) was shown to deliver many transcripts throughout the viral genome (Syed et al, 2021). These findings are consistent with recent theoretical studies that predict multiple packaging signals exist as ~400 nucleic acid repeats (Chechetkin & Lobzin, 2021; Chechetkin & Lobzin, 2022). Although NMR studies that include our own have confirmed that the SARS‐CoV‐2 N protein NTD and flanking regions bind to short RNAs (Dinesh et al, 2020; Redzic et al, 2021), whether the CTD and CTE have similar affinity for short RNAs remains unclear.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…An elegant study employing all four structural proteins to produce viral‐like particles (VLPs) was shown to deliver many transcripts throughout the viral genome (Syed et al, 2021). These findings are consistent with recent theoretical studies that predict multiple packaging signals exist as ~400 nucleic acid repeats (Chechetkin & Lobzin, 2021; Chechetkin & Lobzin, 2022). Although NMR studies that include our own have confirmed that the SARS‐CoV‐2 N protein NTD and flanking regions bind to short RNAs (Dinesh et al, 2020; Redzic et al, 2021), whether the CTD and CTE have similar affinity for short RNAs remains unclear.…”
Section: Introductionsupporting
confidence: 92%
“…We selected these two additional large RNA fragments based on recent reports that indicate 54 n.a. repeats are present throughout the SARS‐CoV‐2 genome that are proposed to form multiple packaging signals (Chechetkin & Lobzin, 2021; Chechetkin & Lobzin, 2022). Each of these new RNA fragments was designed to have 6 of these repeats and thus, comprised 324 nucleic acids that correspond to the viral genome of n.a.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, coarse-graining of various profiles (e.g., AT/GC content, expression profiles, protein binding profiles) results in a set of stretches within which the characteristics exceed some thresholds. Previously, it was shown that the coarse-grained profiles obtained by transitional automorphic mapping of the genome on itself (TAMGI) contain important information about functional regions in viral genomes [ 55 , 56 ]. The colocalization between stretch sets obtained by coarse-graining of profiles can also be treated by the method developed in our paper.…”
Section: Discussionmentioning
confidence: 99%